Outcome of bonded vs all-ceramic and metal- ceramic fixed prostheses for single tooth replacement - Karl, Matthias (European Journal of Oral Implantology, 2016)
The conventional treatment of a single missing tooth is most frequently based on the provision of a fixed dental prosthesis (FDPs). A variety of designs and restorative materials are available which have an impact on the treatment outcome. Consequently, it was the aim of this review to compare resin-bonded, all-ceramic and metal-ceramic FDPs based on existing evidence.An electronic literature search using "metal-ceramic" AND "fixed dental prosthesis" AND "clinical, all-ceramic" AND "fixed dental prosthesis" AND "clinical, resin-bonded" AND "fixed dental prosthesis" AND "clinical, fiber reinforced composite" AND "clinical, monolithic" AND "zirconia" AND "clinical" was conducted and supplemented by the manual searching of bibliographies from articles already included.A total of 258 relevant articles were identified. Metal-ceramic FDPs still show the highest survival rates of all tooth-supported restorations. Depending on the ceramic system used, all-ceramic restorations may reach comparable survival rates while the technical complications, i.e. chipping fractures of veneering materials in particular, are more frequent. Resin-bonded FDPs can be seen as long-term provisional restorations with the survival rate being higher in anterior locations and when a cantilever design is applied. Inlay-retained FDPs and the use of fiber-reinforced composites overall results in a compromised long-term prognosis. Recently advocated monolithic zirconia restorations bear the risk of low temperature degradation.Several variables affect treatment planning for a given patient situation, with survival and success rates of different restorative options representing only one factor. The broad variety of designs and materials available for conventional tooth-supported restorations should still be considered as a viable treatment option for single tooth replacement.
EVALuna2:24826